Analisis Penilaian Hasil Belajar Siswa pada Mata Pelajaran PPKn di Siswa SMP Negeri 2 Sungguminasa Kecamatan Somba Opu Kabupaten Gowa - Andi Sugiati; Jumiati Nur (JED (Jurnal Etika Demokrasi), 2018)
This study aims to determine the planning and management of student learning outcomes assessment in PPKn subjects at Sungguminasa 2 Public Middle School. This type of research is qualitative descriptive research. Data source is RPP document assessment plan. The population in the study were PPKn teachers at Sungguminasa 2 Public Middle School. The research sample was the PPKn teacher class VII.2, VIII.8, and IX.5 Sungguminasa 2 Public Middle School. Data collection techniques used were observation, documentation, and interviews. The research data were analyzed qualitatively descriptive. The results of the study show that (1) Planning for student learning outcomes is in accordance with the 2013 curriculum by reviewing core competencies and basic competencies to achieve assessment indicators in accordance with learning materials including spiritual and social attitudes, knowledge, and skills. The assessment instrument is in the form of assignment of written and non-test tests, namely observation, (2) Management of assessment of learning outcomes is less in accordance with the RPP assessment plan. The teacher assesses spiritual attitudes and social attitudes, uses a journal assessment that is not in accordance with the assessment plan and does not use the assessment rubric so that the assessment indicators are not achieved. Teachers in assessing knowledge with assessment tests are in accordance with the RPP assessment plan and use assessment rubrics so that indicators of knowledge assessment are achieved. Teachers assess skills, use performance that is not found in the RPP assessment plan so that the assessment indicators are not achieved. Teachers who only assess skills with observations without evaluating reports on the results of discussions and project evaluations so that the assessment indicators are not achieved.Keywords : Learning Outcomes Assessment, 2013 Curriculum.